2014
DOI: 10.1016/j.juro.2014.03.101
|View full text |Cite
|
Sign up to set email alerts
|

Combined Chemohyperthermia: 10-Year Single Center Experience in 160 Patients with Nonmuscle Invasive Bladder Cancer

Abstract: Chemohyperthermia is an effective approach to nonmuscle invasive bladder cancer for which standard intravesical treatments fail. Patients with highly recurrent disease before chemohyperthermia have lower recurrence-free survival. Furthermore, recurrence-free survival appears to improve with earlier chemohyperthermia. No significant differences were observed between the 2 chemotherapy agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 17 publications
4
43
0
2
Order By: Relevance
“…6 Even though new treatments have been reported, more results and larger studies are needed. 6,12,[14][15][16] Colombo and colleagues found that C-HT is more effective than MMC alone. 17 The 10-year disease-free survival rate for C-HT and MMC alone were 53% and 15%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…6 Even though new treatments have been reported, more results and larger studies are needed. 6,12,[14][15][16] Colombo and colleagues found that C-HT is more effective than MMC alone. 17 The 10-year disease-free survival rate for C-HT and MMC alone were 53% and 15%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…RF-potentiation is not restricted to MMC alone, but also to other anti-neoplastic agents such as epirubicin [71]. As mentioned earlier [66], the statistically significant superiority of RITE over BCG could possibly lead to a paradigm shift in the treatment of NMIBC, as no treatment was found comparable to the BCG gold standard for 40 years.…”
Section: Rf Applications In the Futurementioning
confidence: 96%
“…This technique also minimizes the inter-patient variability and increases patients' tolerability, and has been used throughout the years with RITE [54][55][56][66][67][68][69][70][71].…”
Section: Pharmacokinetics In Rite and "Dose Splitting"mentioning
confidence: 99%
“…Progression to muscle-invasive bladder cancer occurred in three patients, all treated within the ablative protocol. Arends et al evaluated the efficacy of CHT in 160 patients with NMIBC, refractory to intravesical treatment (MMC, epirubicin, BCG) [29]. Patients were treated with either a prophylactic or an ablative protocol.…”
Section: Post Previous Intravesical Treatmentmentioning
confidence: 99%
“…Posterior wall thermal reaction, a phenomenon typically seen on cystoscopy after microwave-induced CHT, is caused by the location of the RF antenna. It appears as a medallion-shaped discoloured scar-like patch, which in general resolves spontaneously and is not associated with symptoms [9][10][11]21,[23][24][25][26][27][28][29][30].…”
Section: Synergomentioning
confidence: 99%